A Analisis Dampak Penerapan Program Profil Pelajar Pancasila untuk Pencegahan Perkawinan Anak di Kabupaten Lombok Timur - Karomi; Abdul Majid Junaidi (LPPM Universitas Gunung Rinjani, 2023)
The aims of this study are to 1) explore policies related to the Pancasila Student Profile Program so that it has an impact on the decline in the number of child marriages in East Lombok district, 2) to observe the achievements of the implementation of the Pancasila Student Profile on changes in children's behavior so that it has an impact on reducing the number of child marriages in Indonesia. East Lombok district, and 3) to formulate alternative solutions to the problem of preventing child marriage through educational institutions in schools, especially the driving school in East Lombok district. This study uses a qualitative descriptive method with observation, interviews, and documentation techniques. The conclusions generated from this study regarding the analysis of the impact of the application of the Pancasila student profile for the prevention of child marriage in East Lombok district, are as follows: 1) Policies on preventing child marriage in East Lombok district still have not touched education, as a whole, such as school programs, curriculum of the education unit; 2) Strengthening the profile of Pancasila students needs to be carried out in schools in order to change the focus of students from negative activities, thus causing students to fall into child marriage; 3) Strengthening the profile of Pancasila students, as an alternative to create students who think critically so that they are able to filter information that child marriage is the root of social problems in the region; 4) The profile of Pancasila students must have the support of a learning environment so that students are more independent, so that marriage is not just a matter of hoping for a partner, but also there must be a spirit of independence in order to realize the values ​​of gotong royong after adulthood; 5) The Pancasila student profile program is a solution to children's problems, especially child marriage: this study suggests, 1) The need for policies that touch the roots of social problems in East Lombok district; 2) The need to strengthen the profile of Pancasila students through the curriculum of the Education unit.. Abstrak Tujuan penelitian ini adalah untuk: 1) mengeksplor kebijakan terkait dengan Program Profil Pelajar Pancasila sehingga berdampak terhadap menurunnya angka perkawinan anak di kabupaten Lombok Timur, 2) untuk mengamati capaian dari implementasi Profil Pelajar Pancasila terhadap perubahan perilaku anak sehingga berdampak terhadap pengurangan angka perkawinan anak di kabupaten Lombok Timur, dan 3), untuk merumuskan altiernatif pemecahan masalah terhadap pencegahan angka perkawinan anak melalui pendekatan lembaga pendidikan di Sekolah, khusunya sekolah Penggerak di Kabupaten Lombok Timur. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik observasi, wawancara dan dokumentasi. Adapun kesimpulan yang dihasilkan dari penelitian ini tentang analisis dampak penerapan profil pelajar Pancasila untuk pencegahan perkawinan anak di kabupaten Lombok Timur, adalah sebagai berikut: 1) Kebijakan tentang pencegahan perkawinan anak di kabupaten Lombok Timur masih belum menyentuh Pendidikan, secara keseluruhan, seperti program sekolah, kurikulum satuan pendidikan;2) Penguatan profil palajar Pancasila perlu dilakukan di sekolah dalam rangka mengubah fokus peserta didik dari aktivitas-aktivitas negative, sehingga menyebabkan peserta didik terjerumus terhadap perkawinan anak; 3) Penguatan profil pelajar Pancasila, sebagai alternatif untuk mewujudkan peserta didik yang berfikir kritis agar mampu menyaring informasi bahwa perkawinan anak itu merupakan akar masalah social di daerah; 4) Profil pelajar Pancasila mesti harus adanya dukungan lingkungan belajar agar para peserta didik agar lebih mandiri, sehingga menikah itu adalah bukan tentang masalah berharap pada pasangan saja namun juga harus ada jiwa kemandirian agar terwujud nilai-nilai gotong royong setelah dewasa; 5) Program profil pelajar Pancasila menjadi solusi terhadap permasalahan-permasalahan anak, khusunya terhadap perkawinan anak: penelitian ini menyarankan, 1) Perlunya kebijakan yang menyentuh akar masalah sosial di kabupaten Lombok Timur; 2)Perlunya penguatan profil pelajar Pancasila melalui kurikulum satuan Pendidikan. Kata kunci: Profil_Pelajar_Pancasila; Karakter; Perkawinan_Anak